Influence of hot environment on pitching and hitting performance in professional baseball - Huang, J. H.; Chiu, Y. C.; Chang, C. K. (The Journal of Strength and Conditioning Research, 2021)
Baseball is usually played outdoors during the warmest months of the year. The long exposure to a hot environment may lead to hyperthermia and subsequent impaired cognitive function, which is crucial for hitting and pitching performance in baseball. The purpose of this study was to investigate the effect of apparent temperature on pitching and hitting performance in Chinese Professional Baseball League games in Taiwan. Each pitched and batted ball from a total of 480 regular season games in 2018 and 2019 was analyzed. Each game was categorized into one of the 4 groups on the basis of the average apparent temperature at which it was played: cold (below 21° C), warm (21-28° C), hot (28-34° C), or extremely hot (above 34° C). Differences in pitching and hitting variables were compared across the 4 groups. In the extremely hot environment, slugging percentage, isolated power, base on balls per 9 innings, home runs per 9 innings, and walks plus hits per inning were all significantly higher than those in the other 3 environments. The results suggest that offensive production was significantly increased in extremely hot environments in the Chinese Professional Baseball League. It is recommended that pitchers could adopt cooling interventions to alleviate the decline in performance in an extremely hot environment.